Neurobehavioral effect of essential oil of Cymbopogon citratus in mice - Blanco, M. M. [UNESP]; Costa, C. A. R. A. [UNESP]; Freire, A. O. [UNESP]; Santos, J. G. [UNESP]; Costa, M. [UNESP] (Elsevier Gmbh, Urban & Fischer Verlag, 2009)
Tea obtained from leaves of Cymbopogon citratus (DC) Stapf is used for its anxiolytic, hypnotic and anticonvulsant properties in Brazilian folk medicine. Essential oil (EO) from fresh leaves was obtained by hydrodistillation and orally administered to Swiss male mice 30 min before experimental procedures. EO at 0.5 or 1.0 g/kg was evaluated for sedative/hypnotic activity through pentobarbital sleeping time, anxiolytic activity by elevated plus maze and light/dark box procedures and anticonvulsant activity through seizures induced by pentylenetetrazole and maximal electroshock. EO was effective in increasing the sleeping time, the percentage of entries and time spent in the open arms of the elevated plus maze as well as the time spent in the light compartment of light/dark box. In addition, EO delayed clonic seizures induced by pentylenetetrazole and blocked tonic extensions induced by maximal electroshock, indicating the elevation of the seizure threshold and/or blockage of seizures spread. These effects were observed in the absence of motor impairment evaluated on the rotarod and open field test. Our results are in accord with the ethnopharmacological use of Cymbopogon citratus, and after complementary toxicological studies it can support investigations assessing their use as anxiolytic, sedative or anticonvulsive agent. (C) 2007 Elsevier GmbH. All rights reserved.
Keywords: Anxiolytic; Sedative; Anticonvulsant; Cymbopogon citratus; Essential oil; Lemongrass